Effect of high-strength steel spirals on the seismic behavior of square concrete-filled steel tubular columns under high axial load ratio. (15th March 2023) - Yuan, Fang; Li, Zhuowei; Li, Huihui; Feng, Yulin
Highlights: Seismic behavior of 15 square CFST columns were experimentally studied through the cyclic loading tests. Effects of steel spiral pitch and axial load ratio on the hysteretic behavior, energy dissipation capacity, load-carrying capacity, and deformation ability of the HSS-CFST columns were investigated. Effects of steel spiral pitch and axial load ratio on the ductility and stiffness degradation of the HSS-CFST columns were explored. Both the NSS and HSS spirals could improve the hysteretic behavior and energy dissipation capacity of square CFST columns, but the contributions to these improvements made by the HSS spirals are more significant. Increase of steel volume ratio of the HSS spirals could improve the ductility of the HSS-CFST columns and the ductility improvement is even more pronounced under a higher axial load ratio. Abstract: Ductility of square concrete filled steel tubular (CFST) columns is generally significantly lower than that of circular ones, especially when they are under high level of axial loads. Many previous studies suggested that adding internal steel spiral stirrups is an effective measure to improve ductility of square CFST columns. To investigate the effect of high-strength steel (HSS) spirals on the seismic behavior of the HSS spiral-confined CFST (HSS-CFST) columns under high axial load ratio, 15 square CFST columns, including 3 conventional CFST columns without internal steel spirals, 3 normal-strength steel (NSS) spiral-confined CFST (NSS-CFST) columns, and 9 HSS-CFST columns were experimentally studied through the cyclic loading tests. The critical test parameters included the steel spiral pitch and axial load ratio. Final failure modes, hysteretic response, skeleton curves, strain distributions, ductility, energy dissipation capacity, and stiffness degradation of the specimens were investigated in detail. The experimental results indicated that (i) apparent outwardly local bucking of the steel tube and core concrete crushing were observed for all specimens in the plastic hinge regions at the ultimate state; (ii) adding both the NSS and HSS spirals would beneficial in improving the hysteretic behavior and energy dissipation capacity of square CFST columns, but contributions to these improvements made by the HSS spirals were more significant than that of the NSS ones; (iii) the increase of axial load ratio and internal steel spiral pitch would impair the load-carrying capability and ultimate deformation ability of square CFST columns; (iv) ductility of the NSS-CFST and HSS-CFST columns could be improved as the increased of spiral volume ratio and the ductility enhancement was more pronounced in the HSS-CFST columns; and (v) the internal steel spirals were helpful in delaying the stiffness degradation rate of square CFST columns, particularly for those specimens under a high axial load ratio of 0.8.